Fish protein hydrolysate from lemuru (Sardinella lemuru) scales as a food protein: isolation, characterization, antibacterial and antioxidant activities - Susanti, Evi; Firdaus, Jannatul; Hikmah, Safriza Lailatul; Salim, Norazlinaliza; Herdyastuti, Nuniek; Herawati, Elisa; Laily, Noer; Illaningtyas, Fatim; Artasasta, Muh Ade; Putra, Wira Eka (Walailak University, 2026)
Fish protein hydrolysates (FPHs) have attracted significant interest owing to their robust nutritional composition, including glutamic acid, aspartic acid, leucine, lysine, and valine. The scales of lemuru (Sardinella lemuru) are currently underutilized. Therefore, in this research, FPHs from lemuru scales were produced by using papain through various stages including pretreatment of fish scales waste; optimization enzymatically of the FPHs production from waste scales of lemuru fish using papain includes the incubation time and the quantity of papain; characterization includes proximate analysis, FTIR, and SDS-PAGE; and determination of FPHs antibacterial and antioxidant activities. The results showed that the optimum FPHs production at 90 min incubation time with 0.705 U papain produced FPHs as much as 21.43%, with the molecular weight achieved less than 37 kDa. The proximate analysis of the prepared FPHs showed moisture, protein, fat and ash content of 16.85, 36.52, 0.298 and 46.34%, respectively. FTIR results showed that identical hydroxyl, carbonyl, and amide functional groups indicated the presence of peptide bonds. These findings suggest the complete enzymatic hydrolysis, and at the same time the presence of the functional groups supporting the bioactivity potencies of the hydrolysates which are involved in antibacterial and antioxidant activities. Interestingly, FPHs from lemuru scales with a concentration of 10,000 ppm could inhibit the growth of Escherichia coli bacteria indicating clear zone as much as 5.62 ± 0.19 mm and Staphylococcus aureus bacteria was 7.50 ± 0.14 mm. The IC50value for inhibiting DPPH free radical oxidation was 60.441 µg/mL for the FPHs of lemuru scales powder. Thus, in conclusion, the FPHs from the lemuru scales has the potential to be developed as a raw material for food protein with antibacterial and antioxidant activities.